Penguatan Moderasi Beragama Diruang Digital: Studi Moderasi Beragama Di Pondok Pesantren Assunniyyah Kencong Jember - Asnawan, Asnawan; Mukhsin, Mukhsin; Hakim, Faisol; Kholif Rosyidi, Achmad (INAIFAS Press, 2024)
This service aims to carry out a sustainable strengthening of religious moderation challenges in the digital space for students, of course, it is very appropriate to be developed through creating a website or digital platform that can be accessed by all students to obtain information and materials on religious moderation either directly from kiyai or ustad. Use social media, such as Facebook, Twitter, Instagram, or YouTube to share educational materials, sermons, and recitations online. Holding webinars or video conferences with topics relevant to religious moderation and tolerant and inclusive Islamic values. Create podcasts or audio recordings that can be accessed by all students to listen to religious recitation or lectures. Holding competitions or competitions that direct students to produce creative content that supports religious moderation, such as making educational videos or writings containing messages of religious moderation